Nutritional Value of Exogenous Enzyme Supplementation in the Utilization of Cassava Peel Meal-Based Diet by Broiler Finisher Chickens - Aguihe P.C; Ntagbu F.G.; Ilaboya I.I; Ogialekhe P.; Wealth A. S; Ehielu R. O; Okuna R; Kehinde A.S (Contemporary Research and Perspectives in Biological Science Vol. 3, 2024)
The utilization of exogenous enzymes is a prevalent nutritional strategy in the poultry industry. However, their effectiveness when used in diets formulated with non-traditional agro-byproducts like cassava peel remains uncertain. From a practical standpoint, assessing the efficacy of these enzymes in such contexts is vital to achieving competitive performance outcomes while maintaining low production costs. This study assessed the supplemental value of exo-enzyme (Maxigrain®) in the utilization of cassava peel meal (CPM) by broiler finisher chickens in a 28-day feeding trial. Two hundred and forty, 4 weeks old Arbor acre broiler birds were randomly allocated to four experimental diets tagged as T1, T2, T3 and T4, which were formulated to replace maize at 0, 25, 50, and 75% inclusion levels respectively with supplementary enzyme (Maxigrain®). The birds were further subdivided into four replicates of ten birds each in a completely randomized design arrangement. At the end of the 4 weeks feeding trial, performance and carcass attribute indices were measured, while feces and blood samples were collected for nutrient digestibility and blood biochemical evaluations, respectively. Data on feed cost analysis were calculated using the prevailing current market price of feed ingredients. The result showed that average weight gain and feed intake were significantly affected (P<0.05) by dietary treatments. Birds on a 50% CPM enzyme diet had a significant (P<0.05) higher weight gain and feed intake followed by those on a 75% CPM diet as compared to the control group. Feed cost/kg weight gain significantly (P<0.05) decreased with increasing levels of enzyme-supplemented CPM. Profit margins generated were higher (P<0.05) in bird fed enzyme-treated CPM diet group. The apparent nutrient digestibility of the birds revealed a significant (P<0.05) variation in all parameters evaluated and increased with increasing levels of enzyme-supplemented CPM diets. Also, all blood metabolites evaluated were significantly affected (p<0.05) by enzyme supplementation to CPM-based diseases except for WBC, globulin, creatinine and cholesterol. Enzyme supplementation produced no significant (p>0.05) effect on live weight, carcass weight and dress weight across the treatments, however, birds at 50% dietary level had the highest mean values compared to other treatment groups. The cut weights of the wing, breast, thigh, back, liver, GIT and kidney were significantly (P<0.05) affected by the dietary treatments. Therefore, enzyme supplementation improved performance, nutrient digestibility, and carcass characteristics of broiler finishers fed cassava peel meal-based diet without any adverse effect and 50% inclusion gave an optimum performance on carcass and organ traits.